2009
DOI: 10.1111/j.1479-828x.2009.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Opinion: Integration of diagnostic and management perspectives for placenta accreta

Abstract: The 2007 New South Wales/Queensland Royal Australian and New Zealand College of Obstetricians and Gynaecologists Annual Scientific Meeting convened a panel to discuss multidisciplinary perspectives on the management of placenta accreta, percreta or increta. While it was anticipated that this panel would stimulate discussion, the cohesion between the approaches was underestimated. This document represents an integration of the perspectives of the invited speakers at this presentation, with backgrounds in matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 104 publications
(121 reference statements)
0
16
0
Order By: Relevance
“…11 While population studies have confirmed reduced levels of haemorrhage and the need for transfusion with this approach, 12 prior antenatal identification and recognition of this condition remains the pivotal step in improving maternal outcome. Early diagnosis will allow the appropriate multidisciplinary planning and preparation for delivery, 11,12 taking into consideration local resources such as anaesthesia availability, access to intensive care and blood bank services.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 While population studies have confirmed reduced levels of haemorrhage and the need for transfusion with this approach, 12 prior antenatal identification and recognition of this condition remains the pivotal step in improving maternal outcome. Early diagnosis will allow the appropriate multidisciplinary planning and preparation for delivery, 11,12 taking into consideration local resources such as anaesthesia availability, access to intensive care and blood bank services.…”
Section: Discussionmentioning
confidence: 98%
“…11 While population studies have confirmed reduced levels of haemorrhage and the need for transfusion with this approach, 12 prior antenatal identification and recognition of this condition remains the pivotal step in improving maternal outcome. Early diagnosis will allow the appropriate multidisciplinary planning and preparation for delivery, 11,12 taking into consideration local resources such as anaesthesia availability, access to intensive care and blood bank services. Management should include an experienced obstetric team with a specialised surgical network, and can include a gynaecological oncologist (who is further trained in complex pelvic surgery), a urologist (for placement of ureteric stents), as well as a vascular surgeon or an interventional radiologist (for catheterisation and balloon embolisation of internal iliac arteries) to optimise surgical outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…14 Other conservation management can be resection of the myometrium and repairs as described by Palacios et al 15 Though a fully conservative management is possible as suggested by Welsh et al still patient should be warned of the bleeding and infections related risk. 16 We did planned CH in 3 cases and emergency CH in 3 cases. The outcome was much better in planned CH.…”
Section: Discussionmentioning
confidence: 99%
“…A panel convened at the Australian and New Zealand College of Obstetricians and Gynaecologists favours general anaesthesia as providing optimum surgical conditions. 31 Whether neuraxial or general anaesthesia is the optimal technique for these cases will be difficult to establish. Firstly, the number of cases is currently far too small to allow demonstration of the benefits of neuraxial anaesthesia that the Confidential Enquiries have so comprehensively demonstrated for those at lesser risk.…”
mentioning
confidence: 99%